RANKL, OPG and CTR mRNA expression in the temporomandibular joint in rheumatoid arthritis - LIU, WEI-WEI (Exp Ther Med, 2015)
The calcitonin receptor (CTR) and receptor activator of nuclear factor κB ligand (RANKL) have been found to be involved in the differentiation of osteoclasts. The association between the RANKL:osteoprotegerin (OPG) expression ratio and the pathogenesis of bone-destructive rheumatoid arthritis (RA) has been described in several joints, but the available data for the temporomandibular joint (TMJ) are limited. The aim of the present study was to investigate the involvement of osteoclasts at sites of bone erosion by determining the CTR expression and the RANKL:OPG expression ratio in the TMJ in a collagen-induced arthritis (CIA) model. Forty-eight male Wistar rats were randomly divided into two groups: Control group, injected with saline solution for 6 weeks; and CIA group, injected with emulsion. The RANKL and OPG mRNA expression was significantly increased in immunized rats compared with that in non-immunized rats. The RANKL:OPG expression ratio on the trabecular bone surface was 9.0 and 6.4 in the CIA group at weeks 4 and 6, respectively, while the RANKL:OPG expression ratio in the controls was 1.0:2. CTR mRNA expression was significantly upregulated in immunized rats compared with that in non-immunized rats; the level of CTR mRNA in the CTR-positive osteoclasts on the trabecular bone surface was 10.9- and 7.8-fold higher in the CIA rats than that in the control rats at weeks 4 and 6, respectively. In conclusion, focal bone destruction in an experimental model of arthritis in the TMJ can be attributed to cells expressing CTR, a defining feature of osteoclasts. The expression of RANKL and OPG mRNA within the inflamed synovium provides an insight into the mechanism of osteoclast differentiation and function at the border of bone erosion in arthritis.